Macroeconomic effects of secondary market trading - Daniel Neuhann (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
This paper develops a theory of the secondary market trading of financial securitities in which endogenous asset market dynamics generate periods of growing aggregate credit volumes and falling credit standards even in the absence of "financial shocks." Falling credit standards in turn lead to excess risk exposure in the aggregate, precipitating future crises. The credit cycle is triggered by low interest rates, and longer booms lead to sharper crises. Saving gluts and expansionary monetary policy thus lead to financial fragility over time. Pro-cyclical regulation of secondary market traders, such as asset managers or hedge funds, can improve welfare even when such traders are not levered.
Keywords: G01; E32; E44; 330; secondary markets; securitization; credit cycles; financial crisis; financial fragility; credit booms; saving gluts; risk-taking channel of monetary policy